Leaning into politics : higher education and the democracy we need - Goldberg, Abraham (Political science teacher); Whaley, Carah Ong (Research on international civic engagement., 2024)
"Democratic decline in the United States and globally, a lack of confidence in political institutions and an increasingly violent and divisive political climate raise many questions about the state of political learning and civic engagement in higher education. A decade ago, a task force commissioned by the United States Department of Education called on colleges and universities to affirm their missions to educate for democracy. Relatively few have made the investment, though dozens of higher education associations and organizations have publicly committed their support to prepare students to address the persistent public issues they are inheriting. While there has been a recent upward spike in rote civic knowledge and historically high youth voting rates in recent elections, the United States has seen a decline in political rights and civil liberties over the last decade and has been listed as a backsliding democracy. Since 2010, state legislatures have passed laws making it harder to vote, with access to the ballot increasingly dependent on the partisanship of the state legislature. There has also been a rise in the politicization of election administration and extreme partisan and racial gerrymandering. Meanwhile, substantial dysfunction and hyperpartisanship in Congress, concerns over the impartiality of the judiciary and limited accountability and oversight of the executive branch have contributed to the loss of institutional capacity to address pressing public problems and amounted to declining public confidence in political institutions. These trends coincide with problematic rhetoric and growing scrutiny from public officials on how colleges and universities educate students on public issues, particularly those centered on race, ethnicity and social justice. The budgets for some universities have been slashed for promoting such programming while several states have passed legislation targeting related instruction. The issues of free speech and expression were further nationalized following a high-profile hearing of the House Committee on Education and the Workforce that questioned the presidents of Harvard, Massachusetts Institute of Technology and University of Pennsylvania about antisemitism on their campuses. The entire episode served as a loud warning shot to colleges and universities across the country. Academic freedom and freedom of speech - core tenets of a liberal education - are at risk. The first section of this book provides a multifaceted view of the complex relationship between higher education, democracy and societal change. It underscores the need for colleges and universities to navigate and respond to challenging political and economic pressures while maintaining their core democratic and educational values. The second section addresses ways colleges and universities can cultivate a democratic ethos on campuses serving diverse groups of students and the role that public intellectuals can have in a period of democratic decline. The third section focuses on ways to build political efficacy and civic skills such as deliberation, combatting misinformation and fostering student-led efforts. The final section reminds us that colleges and universities are not only preparing political science majors for active and informed participation in democracy, but individuals in every major and discipline. Each chapter contributes to the overarching theme of preparing students for democracy, but they differ in their specific focus areas - from technology and arts to literature and virtual exchange programs, highlighting the multifaceted nature of democratic education. Can higher education step up and meet the moment? Collectively, contributors to this volume, who come from a broad range of institutions, experiences and perspectives provide critical research and analyses, as well as innovative approaches for how higher education can fulfill its public role and contribute to building the democratic societies we need"--